Coulombic interaction in Finnish middle school chemistry: a systemic perspective on students' conceptual structure of chemical bonding. Issue 4 (10th September 2015) - Joki, Jarkko; Lavonen, Jari; Juuti, Kalle; Aksela, Maija
Abstract : The aim of this study was to design a novel and holistic way to teach chemical bonding at the middle school level according to research on the teaching and learning of bonding. A further aim was to investigate high achieving middle school students' conceptual structures concerning chemical bonding by using a systemic perspective. Students in one metropolitan area middle school were introduced to this newly designed model and their conceptual structures were studied by a clinical interview ( n = 8) at the time when the students were concluding their studies at the middle school. The interview data were analysed by employing a systemic perspective on conceptual structures. Elements of conceptual structures such as concepts, simple models (mnemonic devices), explaining schemas, attributes and hypothesis constructs were identified and coded. Connections between the knowledge elements were also identified. An understanding of these connections helps to illuminate which components are necessary to build an adequate conceptual structure. The study revealed that applying principles relating to Coulombic interaction to understand chemical bonding requires the simultaneous appreciation of several factors: First, electron shells have to be understood in terms of energy levels. Second, the distance between the outer electrons and the nucleus has to be understood on the basis of electron shell construction. On the other hand, the effective nuclear charge also needs to be taken into account. The study introduces two new points of view to chemistry education research (CER): (1) a teaching model of chemical bonding that emphasises electric interaction as the background of most bonding types was developed in the study. This responds to the identified need in CER to test alternative teaching models that avoid the octet framework. (2) In the field of chemistry education research, a systemic approach has not previously been widely used for the examination of conceptual structures. In addition, the systemic perception of the network structure, which consists of these constructions, helps to explain in more detail the relationship between the separate concepts and the constructions and their significance as a whole.